2016
DOI: 10.17795/jhealthscope-31766
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality and Health Risks Associated With Exposure to Particulate Matter: A Cross-Sectional Study in Khorramabad, Iran

Abstract: Background: Among ambient air pollutants, particulate matter (PM) has the most undesired adverse effects on human health. Many studies have reported that there is a strong correlation between PM concentrations and hospital admissions due to chronic or acute respiratory and cardiovascular diseases. Objectives: The aims of this study were to evaluate the relationship between air quality and health endpoints of PM 10 in Khorramabad, Iran. Materials and Methods:The PM 10 sampling was carried out with a high-volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…This study used actual cases of morbidity and mortality and concluded that dust particulates were strongly correlated with acute lower/upper respiratory disorders and asthma. This study also revealed that dust storms, suspended dust, rising dust and PM 10 followed a similar pattern throughout the studied period with high peaks during summer months, specifically in June, and lower during winter months; this finding confirms the robust link between dust storm events and ambient air PM 10 levels and is in agreement with other studies in similar arid conditions [6,29,43,44]. Increased PM 10 concentrations during the summer can be associated with the Middle Eastern dust storms from the arid lands of Iraq, Jordan, and Saudi Arabia which are the particular sources of dust events coming to Kuwait from the Northwest [2,29,45].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study used actual cases of morbidity and mortality and concluded that dust particulates were strongly correlated with acute lower/upper respiratory disorders and asthma. This study also revealed that dust storms, suspended dust, rising dust and PM 10 followed a similar pattern throughout the studied period with high peaks during summer months, specifically in June, and lower during winter months; this finding confirms the robust link between dust storm events and ambient air PM 10 levels and is in agreement with other studies in similar arid conditions [6,29,43,44]. Increased PM 10 concentrations during the summer can be associated with the Middle Eastern dust storms from the arid lands of Iraq, Jordan, and Saudi Arabia which are the particular sources of dust events coming to Kuwait from the Northwest [2,29,45].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, all regional Iranian studies [26][27][28][29][30][31][32][33][34][35][36] have used the AirQ 2.3.3 software to model the health impact of short-term exposure to PM 10 ; this software was developed by the WHO to model European morbidity and mortality rates and may overestimate the relative risk and increase prediction error if used by non-European countries because of the obvious higher dust storm events and elevated levels of PM 10 concentrations, especially in the Arabian region. This study used actual cases of morbidity and mortality and concluded that dust particulates were strongly correlated with acute lower/upper respiratory disorders and asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the reduction in longterm exposure to PM 10 concentrations by 5 µg m -3 would have prevented between 3300 and 7700 premature deaths annually, 500 to 1000 of which were associated with shortterm exposure (Medina et al, 2004). Health impacts of air pollution in several cities of Iran have been estimated in several studies using AirQ software (Goudarzi, 2014;Asl et al, 2015;Nourmoradi et al, 2015;Ghozikali et al, 2016;Miri et al, 2016;Mohammadi et al, 2016;Nourmoradi et al, 2016;Khaniabadi et al, 2017). However, only a few of them have considered the health effects of PM 2.5 as a pollutant.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the high number of deaths could be the result of higher PM 10 average or because of sustained highconcentration days in Ahvaz . There are other studies about the application of AirQ 2.2.3 for a variety of air pollutants in different Iranian cities (Goudarzi, 2014;Geravandi et al, 2015;Nourmoradi et al, 2015;Ghozikali et al, 2016;Mohammadi et al, 2016;Nourmoradi et al, 2016;Khaniabadi et al, 2017). However, there has not been a recent analysis of the impacts of each of the criteria pollutants on health outcomes in Tehran, Iran's most populous city.…”
Section: Introductionmentioning
confidence: 99%